Factors that influence the use of credit card: a case study in Negeri Sembilan / Muhammad Afiq Baharin and Nur Liyana Mohd Nizar - Baharin, Muhammad Afiq; Mohd Nizar, Nur Liyana (Faculty of Business and Management, 2014)
This research is to study the demographic factors as the variable that may influence the usage of conventional credit card and also Islamic credit card in Tenaga Nasional Berhad, Seremban and Negeri Roadstone Sdn. Bhd., Nilai. This research helps to determine the pattern of credit card usage and to identify the factors that influent the usage of credit card. The demographic factors such as income level, educational level, marital status, and gender are help to determine which variable are more influence to the usage of credit card in both companies. The data originally consists of 4 dimension data analysis which includes descriptive, frequency, cross tabulation and correlation. The model will help to evaluate the factors that influence respondents’ usage of credit card and to help the bank to know their potential customers and ability customer to pay the debt credit card.